-5(t-9)-(t+5)=2

Simple and best practice solution for -5(t-9)-(t+5)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(t-9)-(t+5)=2 equation:


Simplifying
-5(t + -9) + -1(t + 5) = 2

Reorder the terms:
-5(-9 + t) + -1(t + 5) = 2
(-9 * -5 + t * -5) + -1(t + 5) = 2
(45 + -5t) + -1(t + 5) = 2

Reorder the terms:
45 + -5t + -1(5 + t) = 2
45 + -5t + (5 * -1 + t * -1) = 2
45 + -5t + (-5 + -1t) = 2

Reorder the terms:
45 + -5 + -5t + -1t = 2

Combine like terms: 45 + -5 = 40
40 + -5t + -1t = 2

Combine like terms: -5t + -1t = -6t
40 + -6t = 2

Solving
40 + -6t = 2

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-40' to each side of the equation.
40 + -40 + -6t = 2 + -40

Combine like terms: 40 + -40 = 0
0 + -6t = 2 + -40
-6t = 2 + -40

Combine like terms: 2 + -40 = -38
-6t = -38

Divide each side by '-6'.
t = 6.333333333

Simplifying
t = 6.333333333

See similar equations:

| 8(c+5)-8=80 | | 4(5x-9)=12x+4 | | 2(b+6)-2=16 | | 1+5(x-3)=1-9(x-4) | | 9(z+7)-8=91 | | 8x+12=2x+3 | | 9(x-7)-8=91 | | 3x+19=-2x+4 | | 5(d-4)+5=25 | | 5/6=X210 | | 21=-9+6y | | (M^(4)^(3)(m^(2)^(9)/(m3)^(2) | | 72/60 | | 7+5x=3x-9 | | 80/16 | | z-7/3=4 | | 4+7(x-9)=10-2(x-8) | | 2+6x=3x+11 | | 2-7/3=4 | | 2+x=3x+4 | | -10+60=-h+10000 | | 1/4x-7/8x=15-35 | | x=4x-6*2x+8 | | 24x^2-121= | | 25x^7-123= | | 2*y+3*y=45 | | 9x-5=3xy-8 | | x=4x-6.2x+8 | | 30/45 | | 1.5(x^2)-180x+1000=0 | | -3x+7y=0 | | y=6x(3x+11)+2 |

Equations solver categories